Morphological and phaneroptic traits of Creole goats reared in an extensive system in the dry forest of Tumbes, Peru - Temoche Socola, Victor Alexander; Godoy Padilla, David Jose; Trillo Zarate, Fritz Carlos; Ortiz Morera, Narda Cecilia; Cruz Luis, Juancarlos Alejandro (The Community of Indonesian Biodiversity Society, 2025)
The authors thank the Creole goat producers from Tumbes, Peru who kindly provided samples of their goats for this work. We also thank José Dominguez, David Mena, Harold Ramirez, Reynaldo Becerra, and Alex Casariego for fieldwork assistance. We thank Flor-Anita Corredor for the table editing, thorough review, and insightful comments on this manuscript. To Erwin Urbina for statical assistance and Yunior Garcia for map editing. Finally, we acknowledge the National Institute of Agricultural Innovation (INIA) for its contributions within the framework of the Investment project "Improvement of research and technology transfer services for sustainable management of goat farming in dry forests, in the departments of Tumbes, Piura, Lambayeque, Amazonas, La Libertad, Áncash, Lima, Ica, and Ayacucho" - CUI 2506684.